PERTUMBUHAN JERUK MANIS (Citrus sinensis L.) DENGAN PENAMBAHAN BERBAGAI KONSENTRASI SITOKININ SECARA IN VITRO - Yulianti Rasud; Sri Ulfa; Baharia Baharia (Universitas Tadulako, 2015)
Orange is one of important agricultural commodities with highest position in agroindustry sectors; therefore it is needed a considerable effort to develop the orange plants in a large scale. One of technologies supporting such effort is plant propagation via tissue culture technique. The aim of this experiment was to obtain the most suitable type and concentration of cytokinins for the growth of orange. This experiment was conducted in Plant Biotechnology Laboratory, Faculty of Agriculture, Tadulako University from June to November 2014. This experiment used a Completely Randomized Design with six treatments, namely 0.5 ppm BAP, 1.0 ppm BAP, 1.5 ppm BAP, 0.5 ppm Kinetin, 1.0 ppm Kinetin and 1.5 ppm Kinetin. Data was analyzed using analysis of variance and differences between means of the treatments were determined by Honestly Significant Difference test at 5% level. Results of this experiment indicated that the most suitable type and concentration of cytokinin for the growth of orange was the medium culture supplemented with 1.0 ppm BAP. In such medium composition, the quickest and the highest number of shoot formation was obtained as well as the highest number of leaf formation at 6 weeks after culture, namely 3.40 days after culture, 2.12 shoots and 5.00 leaves per explant, respectively. Keywords : Cytokinin, In Vitro,Orange.